Pengaruh Pemberian Latihan Mc Kenzie Terhadap Perubahan Fleksibilitas Lumbal Pada Lansia Di Panti Wreda Dharma Bakti Surakarta - Nurdianti, Dian, Totok Budi Santoso, S.Fis., S.Pd., M.PH (2017)
Backgroud:Elderly is a part of the process of human growth and development do not suddenly become old, but growing from infants, children, adults, to be old. Elderly will decrease the body's ability to get older, one of which is the reduction of the musculoskeletal system, namely a decrease in lumbar flexibility. The decline of flexibility can lead to limited range of motion (LGS) so the ability of the activity to be limited. As such they should be given that physical exercise Mc Kenzie. Research Objective: To determine the effect of exercise Mc Kenzie to changes in lumbar flexibility in elderly. Research Method: This study used a quasi-experimental approach (quasi) using a design study design pre and post test without control design. Population and sample: The study population is the elderly who live in Hospice Dharma Bakti Surakarta as many as 84 people. Sampling using purposive sampling. With the number of samples in this study as many as 22 people were divided into two groups of 11 people treated group and 11 control group. Results Data analysis: Data were analyzed using the Wilcoxon test to determine the effect of pre and post test in the experimental group. Influence on the different test post test control group and post test treatment using the Mann-whitney test. Statistical test treatment groups at the lumbar flexibility value by Wilcoxon p value = 0.003 <0.005, which means exercise influence on changes in lumbar flexibility in the elderly. On the Mann-whitney test was obtained p = 0.000 <0.005. No different conclusion Mc Kenzie effects of exercise lumbar flexibility to changes in the elderly. Conclusion: There is a Mc Kenzie effects of exercise on lumbar fleksibiitas changes in elderly.